Coronary Palmaz-Schatz stent implantation in acute myocardial infarction. Issue 2 (February 1996) - Neumann, F. J.; Walter, H.; Richardt, G.; Schmitt, C.; Schömig, A.
Abstract : OBJECTIVE: To investigate the feasibility of coronary stenting in acute myocardial infarction. DESIGN: Prospective observational study. PATIENTS: 80 patients undergoing direct balloon angioplasty for acute myocardial infarction who had coronary Palmaz-Schatz stents implanted during a 3 year study period. Indications for stenting were abrupt reocclusion, large dissection with threatened reocclusion, and failure to achieve brisk flow of contrast by angioplasty alone. INTERVENTIONS: After stenting, 50 patients were treated by conventional anticoagulation and 30 patients received antiplatelet therapy with aspirin and ticlopidine. MAIN OUTCOME MEASURES: Death and subacute reocclusion within two weeks. RESULTS: Coronary stenting fully restored vessel patency in 79 patients (98.8%). 10 of 14 patients with symptoms of Killip class IV on admission were discharged from hospital alive. Three of the 66 patients with symptoms of Killip classes I-III died in hospital. Repeat angiography in 59 of these patients, showed 3 symptomatic and 2 silent reocclusions (reocclusion rate 8.5%). No stent thromboses were detected in patients treated with ticlopidine. CONCLUSIONS: Coronary stenting is a safe and effective treatment for complicated direct balloon angioplasty in acute myocardial infarction. In patients with symptoms of Killip classes I to III the risk of subacute reocclusion is comparable to that of bail-out stenting after elective balloon angioplasty.